Design Information System Sales of Nuts and Bolts at PT. Catur Naga Steelindo - Mardiani, Eri; Akbar Ramadhan, Ferdan (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
The company is expected to be able to compete with other companies that market the same product and be able to manage the company well. Companies that are just developing need to develop service regulations to sustain companies that can compete in quality and quality. Because looking at a sale will be good if a business or concrete steps taken can reach the target and can be seen from how to move a product, whether in the form of goods or services, from producers to consumers as the target can be said that sales are one of the activities in the process of fulfilling the needs of sellers and buyers, both in cash and on credit, which companies can carry out to maintain their business so that they develop and to get the desired profit or profit. The primary purpose of sales is to bring profit or profit from the products or goods produced by the producers with good management. Conducting sales is an activity aimed at finding buyers, influencing and giving buyers so that purchases can adapt their needs to the products offered and enter into agreements offered and enter into agreements regarding prices that benefit both parties. In general, sellers or entrepreneurs aim to get a sure profit and maintain or even try to increase it for a long time. This goal can be realized if sales can be carried out as planned